1988
DOI: 10.1111/j.1600-0404.1988.tb05911.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of brainstem lesions in multiple sclerosis: comparison of brainstem auditory evoked potentials with nuclear magnetic resonance imaging

Abstract: Topographical information provided by brainstem auditory evoked potentials (BAEPs) was investigated in 43 patients by comparison with cerebral nuclear magnetic resonance imaging (NMR). Lesions in the region of the brainstem auditory pathways were demonstrated by BAEPs in 44.2%, and in 39.5% by NMR. As regards brainstem levels, in 15/21 (71.4%) with abnormal findings at least one lesion was verified by NMR-matched BAEP results. The study confirms the topographical information provided by the BAEPs on the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

1990
1990
1994
1994

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…The preva lence of BAEP and mSEP abnormalities found in this study is similar to the results in previous reports [3,4,[6][7][8], The lesser sensitivity of EPs than of MRI can be explained by the relatively high anatomic specificity of these tests which analyze BS acoustic pathways and the medial lemniscus. The use of a more extensive battery of neurophysiological techniques, such as electronystagmographic examination, blink reflex, or trigeminal SEP. could probably produce greater sensitivity of neurophysi ological evaluation, as reported by other groups [24][25][26], Our patients had a variety of clinical signs suggestive of focal involvement of BS structures, but in most cases the clinical features cannot be definitely referred to welllocalized lesions.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The preva lence of BAEP and mSEP abnormalities found in this study is similar to the results in previous reports [3,4,[6][7][8], The lesser sensitivity of EPs than of MRI can be explained by the relatively high anatomic specificity of these tests which analyze BS acoustic pathways and the medial lemniscus. The use of a more extensive battery of neurophysiological techniques, such as electronystagmographic examination, blink reflex, or trigeminal SEP. could probably produce greater sensitivity of neurophysi ological evaluation, as reported by other groups [24][25][26], Our patients had a variety of clinical signs suggestive of focal involvement of BS structures, but in most cases the clinical features cannot be definitely referred to welllocalized lesions.…”
Section: Discussionsupporting
confidence: 81%
“…The lower values of BS MRI abnormalities reported in previous papers [6][7][8]10] can be essentially explained by technical difficulties. Several factors may have contrib uted to our positive results: the thickness of the slice, the strength of the field, the combined examination of sagittal and axial planes, and the use of the GMR technique.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The au¬ thors performed brain computed tomog¬ raphy (CT) with and without contrast, and unenhanced brain MRI scans on 10 patients with clinically definite MS (CDMS) . 4 They found 19 periventricular lesions by means of CT scan. All 19 periventricular lesions were also visualized with T2-weighted MRI images, but an additional 112 lesions dis¬ tributed in the periventricular, deep white matter, gray-whitejunction, and the brain-stem regions were visualized by MRI.…”
Section: The Value Of Mri In the Diagnosis Of Msmentioning
confidence: 99%
“…Mariani et al66 reported that 19 The authors found that MS patients with MRI lesions showed a higher CSF IgG concentration, higher number ofCSF plasma cells, and were more likely to have oligoclonal bands com¬ pared with those patients without MRI lesions. Addition¬ ally, there was a higher percentage of peripheral blood cells expressing light chains in patients with abnormal MRI com¬ pared with control subjects.…”
Section: Mri Correlations In Patients With Msmentioning
confidence: 99%